KREATIVITAS GURU PAI DALAM MERANCANG KEGIATAN PEMBELAJARAN PROJEK PENGUATAN PROFIL PELAJAR PANCASILA (P5) PADA SISWA KELAS 8 SMPN 3 KERTEK WONOSOBO - 'Azzam Haikal Makhfudh; Sri Haryanto; Hidayatu Munawaroh (CV. KAMPUS AKADEMIK PUBLISING, 2026)
The Merdeka Curriculum positions the Project for Strengthening the Pancasila Student Profile (P5) as a key instrument in character education through experiential learning. In this context, Islamic Religious Education (PAI) teachers play a strategic role, as they are responsible not only for delivering religious knowledge but also for integrating Pancasila values aligned with Islamic teachings. This study aims to describe the creativity of PAI teachers in designing P5-based learning activities, analyze the achievement of such creativity among eighth-grade students, and identify supporting and inhibiting factors in its implementation at SMPN 3 Kertek Wonosobo. This study employed a qualitative approach with a field research design and a descriptive method. Research subjects included PAI teachers, the school principal, and eighth-grade students. Data were collected through observation, in-depth interviews, and documentation, and analyzed through data reduction, data display, and conclusion drawing. The findings indicate that PAI teachers demonstrated creativity in designing contextual and religiously meaningful project-based learning activities, such as Mosque and School Clean-Up Actions, Ramadan Charity Programs, and Literacy Projects on Tolerant Muslim Figures. The achievements of teacher creativity were reflected in increased student participation, strengthened religious and social character, responsibility, and collaborative literacy skills. Supporting factors included institutional support, teacher motivation, and student enthusiasm, while inhibiting factors involved limited facilities, time constraints, and varying student abilities.